Response surface optimization of the forward extraction of jacalin from jackfruit seeds using AOT/isooctane reverse micellar system - Sy Mohamad, Sharifah Fathiyah; Mohd Said, Farhan; Abdul Munaim, Mimi Sakinah; Mohamad, Shahril; Wan Sulaiman, Wan Mohd. Azizi (Institute of Physics Publishing, 2020)
Jacalin is the major protein contained in the crude extract of jackfruit (Artocarpus heterophyllus) seed that specifically recognizes and binds reversibly to galactose. Conventionally, purification of jacalin is carried out using the tedious and costly chromatographic techniques. In this study, extraction of jacalin from jackfruit seed crude extract were done using the sodium bis(2-ethylhexyl) sulfosuccinate (AOT)-based reverse micellar system. Reverse micellar extraction is an attractive alternative for downstream processing of various proteins. A successful reverse micellar extraction consists of two basic steps: forward and backward extraction. Forward extraction transfers a target protein from an aqueous solution into the reverse micellar solution, while backward extraction releases the protein from the reverse micelles structure into a new aqueous solution. The effects of the aqueous phase pH, NaCl concentration and AOT concentration on the forward extraction efficiency (FEE) are investigated using the response surface methodology (Box-Behnken Design). The main effects and interactions of the parameters are analyzed through the 3D surface plots. The optimum conditions for forward extraction were determined as follows: aqueous phase pH 4.58, 125 mM NaCl and 40 mM AOT. Under the optimal conditions, the FEE reached 88.04±1.30%, closer to 87.99% predicted by the model. The results indicated that AOT/isooctane reverse micelle system is effective in extracting jacalin from the jackfruit seed crude extract and verified the practicability of the BBD model for optimizing the main parameters in the forward extraction of jacalin.